Ecocrítica: orígenes y fundamentos (Crítica) - Balarezo Andrade, Diana Valeria (2022)
Ecocriticism is a field of knowledge that seeks a dialogue between literature and the environment, focusing on the representations of nature in literary production. From this perspective, the document proposes a bibliographical review of different ecocritical studies in order to understand the postulates that sustain this current of thought, from a review of Anglo-Saxon studies to the works produced in Latin America.